Risks vs benefits of nuts consumption in Portugal: the balance between preventable myocardial infarctions and the burden of the liver cancer associated to aflatoxin exposure - Assunção, Ricardo (2019)
The occurrence of mycotoxins in nuts, including the most potent carcinogenic aflatoxins (AFTs), has been reported by several authors worldwide. Notwithstanding, nut consumption plays an important role in the Mediterranean diet due to their nutrient contents and the consequent potential to produce beneficial health effects, as the prevention of cardiovascular diseases. The present study aimed to quantify the health impact in terms of Disability-adjusted life years (DALY) of increasing nut consumption to 30g/day by adult Portuguese population when compared to the current intake.